"Plan de emprendimiento para la implementación de una empresa de ventas de sábanas" - Lizana Laurente, Yennyfer Yannet (2024)
The project proposes the establishment of an entrepreneurship plan for a company specializing in the sale of bedsheet sets. The product will be a basic consumer item with unique features that will make it appealing to consumers. The target demographic will be individuals aged 18 and above from socioeconomic segments A and B in the districts of La Molina, Miraflores, San Borja, San Isidro, and Surco. The production process is crucial for meeting consumer needs and adding value to the product. A reduction in waste is proposed by using surplus fabric from packaging production, thereby promoting an eco-friendly consumer experience. Regarding manufacturing, it will be outsourced to workshops located in the La Victoria district, specifically in the Gamarra area. Chapter 1 introduces the company, theoretical and market frameworks, project motivation, perception of need, idea description and opportunity, justification of business attractiveness, initial strategy, and objectives. Finally, commercial impact and social responsibility are addressed. Chapter 2 presents the ideas, research, and validation of the entrepreneurial solution, including research design and methodology, hypothesis validation, solution validation, population sampling, trend and pattern analysis, and the Business Model Canvas. Chapter 3 defines the strategic planning, which includes the vision, mission, values, and ethics of the company, organizational culture, strategic objectives, external and internal analysis, business success strategy, and concludes with various matrices such as SWOT analysis, EFEM analysis, IFEM analysis, EFE matrix, CPM matrix, and the PEST analysis. Chapter 4 outlines the marketing plan, detailing general objectives, strategies, customer segmentation and profiling, positioning and competitive advantage, target market, market size, target market, and marketing mix strategy development. Chapter 5 defines the operations plan, consisting of operational policies, planning, inventory management, equipment, activities and processes, supplier management, purchasing, stock management, and concluding with outsourcing and process integration. Chapter 6 defines the organizational structure and human resources, including organizational objectives, project structural design, job design and responsibilities, and organizational policies and talent management. Finally, in Chapter 7, the economic-financial plan is detailed, including investment plans, assets and depreciation, working capital, sources of financing and amortization, balance sheet, forecasted income statements, vertical and horizontal income statement analysis, sales projections, and cash flow.